Al-Muhaddith: (Ahmed bin Abdul-Jabbar) Al-Atari Al-Kufi, T. (272) AH, between Al-Jarh and Al-Ta’deel - Ismail, Maher (Humanities Journal of University of Zakho, 2023)
The science of (al-jarh wa ta’deel) is one of the types of hadith sciences related to narrators, and it is of great importance, because the purpose of its knowledge is to memorize the traces and the Sunnah of the Messenger (peace and blessings of God be upon him). Just as the testimony of justice is not accepted, and if knowing the conditions of the narrators is one of the most essential duties to preserve the Sunnah of the Prophet (peace and blessings of God be upon him), then explaining the command of those who are known to be weak or lying, as well as those who are known as “to control” and “justice” is also considered one of that duty, so that people know the truth. Conditions of the hadith of the Prophet (may God bless him and grant him peace) that paying attention to the chain of transmission is one of the characteristics of the Islamic nation. From this point of view, this research came in the presentation and translation of the biography of one of the Mu’ammar Muhaddith: (Ahmed bin Abdul-Jabbar) Al-Atardi Al-Kufi (d. 272 ​​AH), who is considered one of the companions of Imam (Ahmed bin Hanbal) d. (241) AH, and one of the transfers from him from those who heard and spoke about him. To achieve the goal of the research, it was stated: (his name, lineage, birth, elders, and students) and the sayings of scholars about it (wound) and (modification). (Modifiers) In the end, the statements of the two parties were discussed, then reached the final result, which leads to the preference of the (modifying) aspect of the Muhaddith al-Atari over the aspect of (his attack) and thus accepting and invoking his narratives.